Flow Of Container Movement Activities at The Depot PT. Prima Indonesia Logistics - Iqbal Azhari Pane; Dina Rispianti; Fadiyah Hani Sabila (Jurnal Riset dan Inovasi Manajemen, 2024)
The service of container activity flow in the depot that is not carried out effectively will have an impact on the service users which can have a major impact on the company resulting in a reduction in service users in the company. To avoid service users feeling dissatisfied with the depot service, it is better to supervise the activities in the depot and it is necessary to add workers to activities that require fast processing time. The handling scheme for container activity flow in the depot at PT. Prima Indonesia Logistik Belawan starts from container rental and the depot stacking yard. However, in the handling scheme for container activity flow at PT. Prima Indonesia Logistik Belawan, there is still a manual system so that there are often similarities in the numbers in the input lines and have an impact on repeating data input. And damage to the tools that often occur, such as damage to the Reach stacker (Heavy Equipment) which results in hampered activities in the depot. The method used in this study is the Library Research and Field Research methods.